2020
DOI: 10.3390/cells10010054
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Mesenchymal Stem Cells in Regenerative Therapy

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells which can proliferate and replace dead cells in the body. MSCs also secrete immunomodulatory molecules, creating a regenerative microenvironment that has an excellent potential for tissue regeneration. MSCs can be easily isolated and grown in vitro for various applications. For the past two decades, MSCs have been used in research, and many assays and tests have been developed proving that MSCs are an excellent cell source for therapy. This review focusses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 105 publications
1
72
0
7
Order By: Relevance
“…Several lines of evidence demonstrated that efficient tissue repair and regeneration is dependent on the crosstalk between MSCs and Tregs [5,6,22,40,41]. MSCs, in an IDOdependent manner, induce the degradation of tryptophan (TRP) and generation of immunosuppressive kynurenine (KYN) [22].…”
Section: An Interplay Between Mscs and Tregs In Tissue Repair And Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence demonstrated that efficient tissue repair and regeneration is dependent on the crosstalk between MSCs and Tregs [5,6,22,40,41]. MSCs, in an IDOdependent manner, induce the degradation of tryptophan (TRP) and generation of immunosuppressive kynurenine (KYN) [22].…”
Section: An Interplay Between Mscs and Tregs In Tissue Repair And Regenerationmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are self-renewable, rapidly proliferating, multipotent stem cells which reside in almost all post-natal tissues, including quiescent and permanent tissues [5]. MSCs spontaneously differentiate into the cells of mesodermal origin (adipocytes, chondrocytes, and osteocytes) and, under specific conditions, are capable of generating cells of neuro-ectodermal (neurons, astrocytes, and oligodendrocytes) and endodermal origin (hepatocytes) [5]. In addition to their great differentiation potential, MSCs possess potent immunomodulatory and angiomodulatory characteristics [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs are pluripotent stem cells originating from the early mesoderm and ectoderm that have the advantages of abundant availability, multidirectional differentiation potential, high amplification efficiency in vitro and low immunogenicity ( 19 ). In addition, MSCs have powerful immunomodulatory and anti-inflammatory functions, which can regulate the innate immune and acquired immune systems ( 20 ); MSCs also exert bidirectional regulation of the immune system ( 20 , 21 ) and can not only inhibit the overactivated immune system ( 21 , 22 ) but also repair defective immune function ( 23 ). In summary, MSCs can alleviate and repair the lung injury caused by an excessive immune response to viruses and reduce the risk of CSS and ARDS by regulating the function of immune cells, reducing the levels of inflammatory secretion, increasing the levels of anti-inflammatory factors and the secretion a variety of cellular growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…En sık kullanılanlar arasında, mezenkimal kök hücreler bulunmaktadır 13 . Bu durumun sebebi olarak da mezenkimal kök hücrelerden izole edilen mitokondrilerin diğer farklı tipteki hücrelerin mitokondrilerinin rejeneratif etkinliklerinden daha iyi olması ve transplantasyon başarılarının yüksek olması olarak gösterilmektedir 14,15 . Yapılan çalışmalarda izole mitokondrilerin 1-2 saatte alıcı hücrelerin içine girdiği gösterilmiştir.…”
Section: Introductionunclassified